2012
DOI: 10.1186/1756-8935-5-8
|View full text |Cite
|
Sign up to set email alerts
|

The male germ cell gene regulator CTCFL is functionally different from CTCF and binds CTCF-like consensus sites in a nucleosome composition-dependent manner

Abstract: BackgroundCTCF is a highly conserved and essential zinc finger protein expressed in virtually all cell types. In conjunction with cohesin, it organizes chromatin into loops, thereby regulating gene expression and epigenetic events. The function of CTCFL or BORIS, the testis-specific paralog of CTCF, is less clear.ResultsUsing immunohistochemistry on testis sections and fluorescence-based microscopy on intact live seminiferous tubules, we show that CTCFL is only transiently present during spermatogenesis, prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(133 citation statements)
references
References 62 publications
(102 reference statements)
9
124
0
Order By: Relevance
“…Despite the presence of this protein in sperm, to date we have been unable to successfully recover ChIP material, likely due to the unique crosslinking and fragmentation challenges presented by the highly compact sperm nucleus. As an indirect approach to the question of the CTCF footprinting protein, we focused on CTCF-specific and BORIS-specific binding events recently described in ES cells (Sleutels et al, 2012) and asked whether these sites were occupied by short MNase DNA fragments from our sperm dataset. We find that <60bp MNase footprints over CTCF motifs in sperm preferentially occur over sites bound exclusively (in ES cells) to CTCF, while they are completely absent over known CTCFL-only binding sites (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the presence of this protein in sperm, to date we have been unable to successfully recover ChIP material, likely due to the unique crosslinking and fragmentation challenges presented by the highly compact sperm nucleus. As an indirect approach to the question of the CTCF footprinting protein, we focused on CTCF-specific and BORIS-specific binding events recently described in ES cells (Sleutels et al, 2012) and asked whether these sites were occupied by short MNase DNA fragments from our sperm dataset. We find that <60bp MNase footprints over CTCF motifs in sperm preferentially occur over sites bound exclusively (in ES cells) to CTCF, while they are completely absent over known CTCFL-only binding sites (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…BORIS/Boris is present in testis [94,95], indicating a likely role in male germ line establishment [96] and absence of expression results in subfertility [97]. Knockout mice have defects in spermatogenesis with dramatically reduced expression of the cerebroside sulfotransferase (Cst) gene, which is known to play a crucial role in meiosis [98].…”
Section: Franco Et Almentioning
confidence: 99%
“…Other genetic variants have been identified that alter the genetic map in humans: (1) CTCFL, the testis-specific paralog of CTCF, a Zn-finger protein organizing chromatin loops with cohesins (Sleutels et al 2012), (2) the meiosis-specific cohesin RAD21L, which plays a role in the formation of meiotic chromosome axis and synapsis, (3) the SUMO ligase RNF212, ubiquitin ligase HEI10 (CCNB1IP1), and MutS homolog MSH4, all related to members of the ZMM class of pro-CO factors identified in S. cerevisiae, although with different synapsis defects (Reynolds et al 2013;Kong et al 2014;Qiao et al 2014). Strikingly, significant differences are seen among these genetic variants, as those having a large impact on recombination rates have no effect on hotspot usage.…”
Section: Multiple Layers Of Control Shape the Dsb Distribution: Clustmentioning
confidence: 99%